Pengembangan LKPD Berbasis Discovery Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas VIII SMPN 4 Mataram - Hidayah, Amanatul; Subarinah, Sri; Pramestie Wulandari, Nourma; Baidowi, Baidowi (FKIP Universitas Mataram, 2024)
This study aims to produce students worksheet based of discovery learning to improve the problem solving ability of grade 8th student at Junior High School 4 Mataram on the subject of system of two variables linear equations that are valid, practical, and effective. This research is research and development (R&D) using ADDIE development model (Analysis, Design, Development, Implementation, And Evaluations). The subjects were 32 students. Data collection was carried out using a questionnaire and student problem solving abilities test. Data analysis techniques use validity, practicality and effectiveness testing. The result shows that:1) Students worksheet based on discovery learning on the subject of system of two variables linear equations has valid categories, with the results was 84%. 2) The practicality at 90% was in excellent categories, and 3) The effectiveness at 0,71 was in good categories. Based on these results, it was concluded that students'' worksheets based of discovery learning have been valid, practical, and effective, and can be used in learning activities to improve problem solving ability of students.